Dataset of transcriptomic changes induced by naringenin treatment in MCF-7 breast cancer cellsGene Expression Omnibus - Van T. Hoang; Mackenzie L. Hawes; Jack R. Elliott; Steven Elliott; Binghao Zou; Stephen M. Boué; Brian G. Rowan; Bridgette M. Collins-Burow; Jorge A. Belgodere; Muralidharan Anbalagan; Elizabeth C. Martin; Matthew E. Burow (Data in Brief)
Naringenin (Nar) is a citrus fruit-derived phytoestrogen, a group of dietary compounds produced by a wide variety of plants. Due to structural similarity to 17‐β‐estradiol (E2), phytoestrogens can bind to estrogen receptors (ERs) to exert context-dependent estrogenic and/or anti-estrogenic effects. As such, there are potential health benefits and risks associated with phytoestrogen exposure. To investigate the effects of Nar in breast cancer, based on its activity as a phytoestrogen, we treated MCF-7 ER-positive (ER+) breast cancer cells with Nar (10 µM) and examined transcriptomic changes in MCF-7 cells induced by Nar treatment. Pathway analysis included in our dataset shows upregulation of genes associated with estrogen signaling and epithelial-to-mesenchymal transition in breast cancer cells treated with naringenin.